Transport and deposition of mud in deep‐water environments: Processes and stratigraphic implications. Issue 7 (17th June 2019) - Boulesteix, Kévin; Poyatos‐Moré, Miquel; Flint, Stephen S.; Taylor, Kevin G.; Hodgson, David M.; Hasiotis, Stephen T.
Abstract: Deep‐water mudstones are often considered as background sediments, deposited by vertical suspension fallout, and the range of transport and depositional processes are poorly understood compared with their shallow‐marine counterparts. This study presents a dataset from a 538·50 m thick cored succession through the Permian muddy lower Ecca Group of the Tanqua depocentre (south‐west Karoo Basin, South Africa). This study aims to characterize the range of mudstone facies, transport and depositional processes, and stacking patterns recorded in deep‐water environments prior to deposition of the Tanqua Karoo sandy basin‐floor fans. A combination of macroscopic and microscopic description techniques and ichnological analysis has defined nine sedimentary facies that stack in a repeated pattern to produce 2 to 26 m thick depositional units. The lower part of each unit is characterized by bedded mudstone deposited by dilute, low‐density turbidity currents with evidence for hyperpycnal‐flow processes and sediment remobilization. The upper part of each unit is dominated by more organic‐rich bedded mudstone with common mudstone intraclasts, deposited by debris flows and transitional flows, with scarce indicators of suspension fallout. The intensity of bioturbation and burrow size increases upward through each depositional unit, consistent with a decrease in physicochemically stressed conditions, linked to a lower sediment accumulation rate. This vertical facies transition in the single well dataset can be interpreted to represent relative sea‐level variations; the hyperpycnal stressed conditions in the lower part of the units were driven by relative sea‐level fall, and the more bioturbated upper part of the units represent backstepping, related to relative sea‐level rise. Alternatively, this facies transition may represent autogenic compensational stacking. The prevalence of sediment density flow deposits, even in positions distal or lateral to the sediment entry point, challenges the idea that deep‐water mudstones are primarily the deposits of passive rainout along continental margins.